Classification of mechanical prosthetic heart valve sounds. (1st January 2013) - Zhang, Di; He, Jiazhong; Jiang, Yueping; Du, Minghui
Heart sounds of patients are usually used for analysis by cardiologists for the purpose of early detection of various heart diseases. In this paper, Hilbert-Huang transform (HHT) is applied to analyse five different kinds of mechanical prosthetic heart valve sounds, and an HHT-based feature extraction procedure is also developed to classify these five different mechanical heart valve sounds.